(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article notes that the future political, legal, social, economic and international community is of great importance in the formation of constitutional reforms and their legal support for human dignity. It also takes into account the importance of human interest in communicating the goals to the next generation in accordance with their values.